Respuesta :
OK...I saw the original question with variables. Using subtraction we get...
y = -1/2x +4 ... 1/2x + y = 4 (add x to both sides so equations are same)
3x - 6y = 12
multiply first equation by 6 to be able to subtract 6(1/2x +y = 4)
new equations..... 3x + 6y = 24
3x - 6y = -12 (subtract two equations...
6x = 12 (divide by 6 we get x = 2.
substitute x into original equation to get y...
y = -1/2x + 4
y = -1/2 (2) + 4
y = -1 + 4
y = 3 answer (2, 3)
y = -1/2x +4 ... 1/2x + y = 4 (add x to both sides so equations are same)
3x - 6y = 12
multiply first equation by 6 to be able to subtract 6(1/2x +y = 4)
new equations..... 3x + 6y = 24
3x - 6y = -12 (subtract two equations...
6x = 12 (divide by 6 we get x = 2.
substitute x into original equation to get y...
y = -1/2x + 4
y = -1/2 (2) + 4
y = -1 + 4
y = 3 answer (2, 3)